To the question of decision making in physical rehabilitation - Andrii Hertsyk (Kharkiv State Academy of Physical Culture, 2015)
Purpose: searching for a solution of the problem of coordination in a complex hierarchical systems, and study of the mechanism of decision making in physical rehabilitation. Material and Methods: modern approaches to the management of complex hierarchical systems were reviewed; the job descriptions of a physician and instructor of physical therapy were analyzed. Results: centers and stages of decision making in physical rehabilitation were defined by decomposition method, ways to improve coordination in decision making were suggested. Conclusions: the mechanism of decision making in physical rehabilitation requires improvement.